Robust Quantum Computing in Decoherence-Free Subspaces with Double-Dot Spin Qubits - 冯志波 张春丽 周运清 (Communications in theoretical physics, 2014)
We present a scheme for implementing robust quantum gates in decoherence-free subspaces （DFSs） with double-dot spin qubits. Through the resonator-assisted interaction, the controllable interqubit couplings can be achieved only by adjusting the qubit transition frequencies. We construct a set of logic gates on the DFS-encoded qubits to eliminate the collective noise effects, and thus the gate fidelities can be enhanced remarkably. This proposal may offer a potential approach to realize the robust quantum computing with spin qubits.